BROADCAST MEDIA COVERAGE OF 2022 FLOOD IN OGUTA AND OHAJI/EGBEMA LGAs, IMO STATE - Cosmas Nwoga, Chibuzor; OnonujuNwankiti, Chukwuemeka; Rose Chime- Nganya, Chioma; Obin Ogbin, Ogban; Lynda Ngwu, Ogonnaya (African Journal of Social and Behavioural Sciences, 2024)
The thrust of this study was to evaluate broadcast media stations’ reportage of flooding in Nigeria, using Oguta and Ohaji/Egbema LGAs of Imo State as reference points. The study anchored on the Framing theory adopted the content analysis method to evaluate flood disaster stories in NTA, Owerri and IBC, Owerri. 244 programme guides of the two stations from July 2022 to October 2022 were chosen. A sample size of 56 was determined using the composite or construct week method. Findings showed that the main format usually adopted by the broadcast media for reportage of flood disasters was the Straight news; the tone of flood disaster stories evokes fear and panic; the quality of flood stories covered were unbalanced; the broadcast stations do not adequately cover the causes, impact, and strategies to curb flood disasters in their reportage. Recommendations were that NTA, Owerri and IBC, Owerri, as well as other broadcast media in Nigeria, should minimise the use of straight news and adopt more feature presentations/documentaries, opinions/interviews; their news and reports of flood disasters should be framed and presented in such a way that it would instil hope, trust and preparedness, not evoke fear, panic, and anxiety, to the people; they should avoid “afghanistanism” and balance their news reportage; and there should be a synergy between the broadcast media, Federal and State emergency and rescue agencies to warn and educate the public about flood disasters.